Awareness of breast cancer among university female students in Baghdad - Ahmed, Abrar A R (AL-Kindy College Medical Journal, 2019)
Background: Breast cancer still a major cause of disability and mortality among women throughout the world. Lack of awareness and early detection programs in developing countries is a main reason for escalating the mortality. Objectives: to assess level of awareness about breast cancer among university female students in Baghdad focusing on knowledge of breast cancer risk factors, warning symptoms and signs and knowledge about the screening method specially breast self-examination. Methods: A cross-sectional study conducted over two months from first of march through April 2015 and included (240) female students in non- medical colleges at Al-Rusafa and Al-Karkh districts who completed a comprehensive self-structured questionnaire covering socio-demographic characteristics and (27) questions covering the knowledge of risk factors; warning symptoms and signs of breast cancer and the breast self- examination. Participants’ responses were analyzed statistically and percent score of knowledge level was calculated. Results: The mean age of students was (22.8 ± 3.4) years with range (19-30) years, single (75.8%), and those with no family history of breast cancer (85.42%); the internet was the most common source of students’ information (34.7%). Conclusion: The overall percent score of all students’ knowledge about risk factors, warning symptoms and signs and breast self-examination was poor (<60%).